Analisis Keterampilan Menulis Deskriptif Dalam Membuat Poster Berorientasi Pada Inklusi Sosial - Yuanka, Vania Puteri; Kumalasani, Maharani Putri; Ulum, Bahrul (Jayapangus Press, 2025)
This research aims to analyze the use of descriptive sentences based on social inclusion in learning in elementary schools. Descriptive writing skills are very important for elementary school students to have. P5 activities aim to shape students' character and abilities through contextual learning experiences. In a situation like this, making a poster is one thing that can be done. Descriptive writing skills are very important when creating posters because posters are a visual medium that is often used to convey information, and descriptive writing can provide an in-depth explanation of the topic being presented. The research method used is qualitative, with data collection techniques through observation, namely by making observations during the process of making posters in class, in-depth interviews with teachers as the main source of information, and documentation. The focus of the research is to determine students' skills in making descriptive sentences with the theme